Studies of a microporous membrane for analyte preconcentration and separation - Jacob, Silvana do Couto (1994)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Departamento de Entomologia. Rio de Janeiro, RJ, Brasil.